2018
DOI: 10.7717/peerj.5203
|View full text |Cite
|
Sign up to set email alerts
|

Microarray gene expression profiling in colorectal (HCT116) and hepatocellular (HepG2) carcinoma cell lines treated withMelicope ptelefolialeaf extract reveals transcriptome profiles exhibiting anticancer activity

Abstract: BackgroundWe have previously reported anticancer activities of Melicope ptelefolia (MP) leaf extracts on four different cancer cell lines. However, the underlying mechanisms of actions have yet to be deciphered. In the present study, the anticancer activity of MP hexane extract (MP-HX) on colorectal (HCT116) and hepatocellular carcinoma (HepG2) cell lines was characterized through microarray gene expression profiling.MethodsHCT116 and HepG2 cells were treated with MP-HX for 24 hr. Total RNA was extracted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…CCNA2 activates CDK1 at the end of interphase to facilitate the onset of mitosis, and CCNA2 overexpression has been reported in numerous types of cancers. 49 A previous study indicated that CCNA2 amplification and overexpression is associated with carcinogenesis of transgenic mouse liver tumors. 50 Moreover, research has demonstrated that inhibition of CCNA2 can arrest HCC cell proliferation and tumorigenesis.…”
Section: Discussionmentioning
confidence: 98%
“…CCNA2 activates CDK1 at the end of interphase to facilitate the onset of mitosis, and CCNA2 overexpression has been reported in numerous types of cancers. 49 A previous study indicated that CCNA2 amplification and overexpression is associated with carcinogenesis of transgenic mouse liver tumors. 50 Moreover, research has demonstrated that inhibition of CCNA2 can arrest HCC cell proliferation and tumorigenesis.…”
Section: Discussionmentioning
confidence: 98%
“…The dual role of HMOX1 depends on different pathological conditions of cancers [3]. Different cancers have different pathological characters because of distinct abnormalities or dysregulations of genes [19]. Cephalosporin antibiotics regulate the expression of HMOX1 and affect the proliferation of cancer cells differently in different cancers in our previous study.…”
Section: Introductionmentioning
confidence: 72%
“…Multiple drug resistance is, however not restricted to ABC transporters and other MDR phenomena have also been described, including, p53, Bcl-2, the proliferation rate of tumors and others (Efferth et al 2008 ; Hientz et al 2017 ; Reed 1995 ). Microarray analyses were previously performed for HCT116 cell line (Bhattacharjee et al 2005 ; Kabir et al 2018 ; Khonthun et al 2020 ; Ma et al 2017 ), but the application of genomics and transcriptomics methods to isogenic knockout cells allows a superior and deeper comparison between cell lines to identify novel drug resistance mechanisms.…”
Section: Introductionmentioning
confidence: 99%